Smart cities : reality or fiction - Rochet, Claude (London, UK : ISTE, Ltd. ; Hoboken, NJ : John Wiley & Sons, Inc., 2018)
The intelligence of a city is the capacity to learn: to learn the past, its history and the culture of its territory. Unlike the smart city, we do not build a city from scratch and there is nothing, there is no smart city standard car intelligence is measured this ability to fit into a territorial dynamic, a story and a culture. Continuous learning through instantaneous feedback provides the digital to understand and map the urban system and driver.
Foreword -- Introduction -- What do we mean by "Smart city" and where does this idea come from? -- The challenges of urban development in the context of the third industrial revolution -- What makes a city smart -- New sciences of cities -- Smart city in action -- Conclusion.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed September 05, 2018).
John Wiley and Sons
Keywords: Cities and towns -- Technological innovations; City planning -- Technological innovations; Information technology -- Economic aspects; Villes -- Innovations; Technologie de l'information; SOCIAL SCIENCE -- Sociology -- Urban; City planning -- Technological innovations; Information technology -- Economic aspects